Stability and control in a stochastic model of malaria population dynamics - Witbooi, Peter J.; Maku Vyambwera, Sibaliwe; van Schalkwyk, Garth J.; Muller, Grant E. (Advances in continuous and discrete models, 2023)
This article proves a stability theorem for the disease-free equilibrium of a stochastic differential equations model of malaria disease dynamics. The theorem is formulated in terms of an invariant which is similar to the basic reproduction number of a related deterministic model. Compared to the deterministic model, stability of the disease-free equilibrium holds more generally for the stochastic model. The optimal control theory is applied to the stochastic model, revealing some important new insights. Theoretical results are illustrated by way of simulations.